Experimental and CFD analysis of plain and dimples tube at application of solar water heater. (2021) - Arun, M.; Barik, Debabrata; Sridhar, K.P.; Vignesh, G.
Abstract: Solar based water heater takes on a key role in Energy management. Because of its performance, it is more than electric transformation. It has become the much-demonstrated and built-up tool in a large number of families in India to provide boiling water prerequisites. Solar assisted water heating is a very easy and effective approach to receiving and using the Solar's energy. It has a conscious position among the energy clients, regardless of its low efficiency. Every progress in the design and experimental of the solar based -powered water heating system would therefore result to reduction of ordinary fuel and costs. The objective of this solar water heater is to enhance the thermal performance throughout the flat plate collector tube. Furthermore, to reduce the heat loss and to improve the heat transfer by modifying the geometric profile of riser tube. To generate the turbulence flow throughout riser tube to get a better heat transfer on the solar system. The modification of geometry is to create dimples inside the riser tube. The dimple is placing a circular type along the riser tube throughout its surface. Finally, the heat transfer is improving by the modifying riser tube. Finally, the experimental result is analysed with CFD software and the results are compared with the experimental solar water heater.